Obesogenic Environment?. Personal decisions, and institutional and government responsibility: Haslam, D. W. – A.M. Sharma, A. M. – le Roux C. D. (eds.) (2014): Controversies in Obesity. London: Springer-Verlag. (Szociológiai Szemle, 2023)
-